The Changing Role of Gender in Contemporary Muslim Families - Karimullah, Suud Sarim; Ruchiat Nugraha, Aat; Andini, Yokke; Shofiyatun Nisa’, Ihda (Martabat: Jurnal Perempuan dan Anak, 2023)
In the modern era, gender roles in Muslim families have undergone a striking transformation, giving rise to exciting new dynamics in a society previously dominated by tradition. This study explores these changes using literature study methods through integrative and comprehensive literature analysis in collecting, evaluating, and integrating findings from previous studies that are relevant to the topic of study. The study's results stated that the change in gender roles in Muslim families today reflects social, cultural, and religious evolution. This brings balance and inclusiveness between men and women regarding family responsibilities and individual aspirations. Religious influences, especially in Islam, provide a framework that supports diverse interpretations of gender roles. Despite challenges and resistance, especially from groups that held traditional values, these changes increased family well-being, political participation, and economic growth. Greater gender equality in Muslim societies requires education, awareness, and mutual support. With commitment, these changes can lead Muslim communities towards inclusivity, gender justice, and benefits for all members.